PELATIHAN ENGLISH CONVERSATION BAGI TENAGA PENDIDIK DI UNIVERSITAS NAHDLATUL ULAMA PURWOKERTO - M. Happy Nur Tsani; Asfi Aniuranti; Asep Budiman (LPPM Universitas Bina Bangsa, 2021)
English as an international language has a vital role in the development of an institution, especially in communication. English Conversation training for academic staff at UNU Purwokerto was held to train and get used to using English on campus to achieve the goal of becoming a world-class university. The training is intensive with the lecturing methods, question and answer, discussion, problem-solving, practice, and evaluation. Participants are very participatory in training. From the three practice activities, the average speaking ability of the participants increased in each practice. The average value in the first practice was 67. Then, the average increased to 74 in the second practice and 80 in the last practice. There is about a 19.40% increase from initial practice to last practice. In addition, the results of the questionnaire also showed a positive response from the participants. The highest percentage for each item in the questionnaire is on a scale of 4 and 5